Zooxanthellae Life Model and Massalization Growth in the Artificial Environment Waters - Pujiono Wahyu Purnomo (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2010)
Zooxanthellae are part of the phototropic dinoflagellates. This organism  always live as symbiotically with several marine invertebrates. Relationship between zooxanthellae and coral are mutualistic with the transfer nutritif and phisiologis character. With this character, no coral can live without zooxanthellae. Zooxanthellae have vital control on the coral and sessile life. Model of relationship between zooxanthellae and coral are adopted in the artificial environment for take the massalization culture zooxanthellae in the artificial environment. This study was purposed to : (a) Evaluating of environment limiting factors to support optimum growth of zooxanthellae in the artificial environment; (b) Evaluating of purification culture of zooxanthellae and (c) Formulating nutritif to maintenance of maximum gorwth of zooxanthellae. The experiment took place in Natural food and Genetic laboratory of Main Centre of Brackishwater Aquaculture Development Jepara from August 2004 to September 2005. The result showed that: (a) The optimum irradiance for growth of zooxanthellae is green radiance (with comparison 490 - 550 nm); (b) The optimum temperature for growth of zooxanthellae are 20 – 25oC and (c) Adding of 200 µM NaNO3 with repeat again for 16 days,   Key Words: Zooxanthellae, Life Model,Massalization Growth